A semi-active variable equivalent stiffness and inertance device implemented by an electrical network. (July 2021) - Ning, Donghong; Du, Haiping; Zhang, Nong; Jia, Zhijuan; Li, Weihua; Wang, Yafei
Highlights: This paper proposes a variable equivalent stiffness and inertance (VESI) device with an electrical network. The VESI device prototype is built and tested to validate its capability. The VESI device is applied in the vehicle to control the vibration and prevent rollover. Abstract: Semi-active devices have been widely investigated and applied due to their advantages in control systems. However, for satisfying complicated applications, some semi-active devices need to be capable of controlling multiple mechanical properties, which is hard to implement with a mechanical network considering the space limitation. In this paper, a semi-active variable equivalent stiffness and inertance (VESI) device is developed by an electrical network and an electromagnetic device instead of a mechanical system. Due to that the inerter and spring can store energy, the dynamic control of their mechanical properties without the external power to compensate the stored energy will cause the system discontinuity, which will affect the control performance. Therefore, the variable damping (VD) device is applied to connect with spring or inerter in series to obtain variable equivalent stiffness or inertance properties. Then, according to the force-current analogy, an electrical "VESI" network is designed to simulate the mechanical VESI network. An electromagnetic device equips with the variable electrical system can achieve the VESI mechanical properties, which is validated with experiments. The imaginary part of the admittance of the proposed device can vary to the positive phase and also the negative phase by controlling two resistors. The application of VESI device in the vehicle is investigated and analysed. A semi-active control strategy is designed for vibration control and rollover prevention of vehicles with VESI suspensions. According to the simulation result, the proposed semi-active system can significantly improve the vibration reduction performance at both vertical and roll directions; also, it can decrease the roll angel when vehicles in the cornering maneuver. Besides, the semi-active VESI device with an electrical network has the advantages in installation and maintenance. It has great potential in practical applications.